Gender roles among small-scale livestock producers in Costa Rica - Arora, Diksha; Twyman, Jennifer (2018)
As the evidence grows about the critical role of women in agriculture, more and more agricultural development pro-grams and projects aim to address the gender-based constraints to achieve their goals. The process starts with identification of the roles played by men and women in different agricultural activities. The main questions in iden-tifying the roles include - what are the main activities of men and women on- and off-farm and how these activities contribute to production?; do men and women make produc-tive decisions jointly?; do women have access to re-sources?. In case of livestock activities, the evidence on the roles and responsibilities of men and women is lim-ited, particularly in Latin America. As more attention is tar-geted to increasing productivity in the livestock sector in Latin America, there is a greater need to increase the evi-dence on gender roles and intra-household decision-making process among livestock producers in this region.